Engineered miR-214 enriched Schwann cell-derived extracellular vesicles amplify therapeutic efficacy for peripheral neuropathy in T2D mice - Wang, Lei; Lu, Xuerong; Szalad, Alexandra; Zhang, Yi; Li, Yanfeng; Lu, Mei; Kemper, Amy; Liu, Zhongwu; Liu, Xian Shuang; Chopp, Michael; Zhang, Zheng Gang (Frontiers in Cellular Neuroscience, 2025)
Extracellular vesicles (EVs) derived from healthy Schwann cells (SC-EVs) ameliorate peripheral neuropathy in diabetic mice and rescue sciatic nerve function in Schwann cell Dicer knockout mice in part via SC-EV cargo miRNAs. Among these miRNAs, miR-214 repairs nerve damage. The present study investigated whether engineered SC-EVs with elevated miR-214 (214-EVs), further amplify the therapeutic effect of naïve SC-EVs (naïve-EVs) on reducing diabetic peripheral neuropathy (DPN) in a mouse model of high-fat diet (HFD)-streptozotocin (STZ) induced type 2 diabetes. Compared to naïve-EVs, 214-EVs significantly improved motor and sensory nerve conduction velocity of the sciatic nerve and thermal latency, which were associated with increased intraepidermal nerve fiber density, axonal diameter, and myelin thickness in the sciatic nerve. Quantitative RT-PCR and Western blot analyses of sciatic nerve tissues showed that, compared to naïve-EVs, 214-EVs significantly increased miR-214 levels and downregulated axonal inhibitory protein PTEN and the myelination inhibitory protein cJUN. Furthermore, 214-EVs markedly suppressed neuroinflammation by decreasing CD68 + macrophages and inactivating the TLR4/NF-κB signaling pathway. Collectively, our findings demonstrate that miR-214-enriched SC-EVs are superior to naïve-EVs to ameliorate DPN and represent a promising EV-based therapeutic strategy.